2013
DOI: 10.1016/j.vaccine.2013.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Duration of protection against hepatitis A for the current two-dose vaccine compared to a three-dose vaccine schedule in children

Abstract: Background-Hepatitis A is mostly a self-limiting disease but causes substantial economic burden. Consequently, United States Advisory Committee for Immunization Practices recommends inactivated hepatitis A vaccination for all children beginning at age 1 year and for high risk adults. The hepatitis A vaccine is highly effective but the duration of protection is unknown.Methods-We examined the proportion of children with protective hepatitis A antibody levels (anti-HAV ≥20 mIU/mL) as well as the geometric mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…6 It is highly immunogenic conferring protection against HAV in approximately 95% of the vaccinated travelers. 7 Protection is considered to be lifelong after a complete hepatitis A vaccination schedule (two doses) 8,9 and a combined hepatitis A/B vaccine is also available in some countries. 10 Routine vaccination of children is an effective way to reduce hepatitis incidence in developed countries, however only some of them had implement it in the national immunization program as a mandatory vaccine or considered it for some risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is highly immunogenic conferring protection against HAV in approximately 95% of the vaccinated travelers. 7 Protection is considered to be lifelong after a complete hepatitis A vaccination schedule (two doses) 8,9 and a combined hepatitis A/B vaccine is also available in some countries. 10 Routine vaccination of children is an effective way to reduce hepatitis incidence in developed countries, however only some of them had implement it in the national immunization program as a mandatory vaccine or considered it for some risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of these analyses was waning of hepatitis B vaccine-induced antibody to levels no-longer defined as protective [28]. In contrast, after hepatitis A vaccination, anti-HAV has persisted in the majority of responders since vaccines were approved for use in 1995–1996; mathematical modeling suggests persistence of vaccine-induced anti-HAV might be ≥25 years in as many as 95% of the population [2932]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of reduced dose schedules in vaccinology is not unusual as other vaccines such as Pneumococcal, Hepatitis A and Meningococcal C dosing schedules have been revised from three to two doses, following clinical studies that have demonstrated noninferiority in immunogenicity and safety [36][37][38]. High costs of HPV vaccines and logistical issues with delivery, together with higher antibody responses observed in young adolescents, has prompted the exploration of reduced dose HPV schedules.…”
Section: Evidence Of Non-inferior Antibody Responses In Reduced Dosementioning
confidence: 99%